Bungur Medika Hospital Business Model: Review based on Value Proportional Canvas Perpestives - Indah Maulina Dewi; Tantri Yanuar Rahmat Syah; Ratna Indrawati Lestariani; Agus Munandar (Syntax Corporation Indonesia, 2023)
-